Transient reversal of macular ischemia with intravitreal steroid implant injection in a case of radiation maculopathy - Verma, Aditya (Indian J Ophthalmol, 2018)
Diabetic retinopathy (DR) is a well-known risk factor in the development of radiation maculopathy (RM). Steroids have been shown to improve the vision and reduce the macular thickness in patients with RM. This observational case report highlights altered course of DR after a course of radiotherapy for orbital lymphoma, after a single dose of intravitreal dexamethasone implant showed a dramatic revascularization of the ischemic macula, with a significant reduction in the size of ischemic area. This appears to be the first case in literature corroborating the favorable effect on steroids on retinal vasculature, seen angiographically.